2014
DOI: 10.1111/1462-2920.12430
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and dynamics of a groundwater and a still bottled natural mineral water

Abstract: The microbial abundance and diversity at source, after bottling and through 6 months of storage of a commercial still natural mineral water were assessed by culture-dependent and culture-independent methods. The results revealed clear shifts of the dominant communities present in the three different stages. The borehole waters displayed low cell densities that increased 1.5-fold upon bottling and storage, reaching a maximum (6.2 × 10(8)  cells l(-1) ) within 15 days after bottling, but experienced a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 55 publications
8
30
1
Order By: Relevance
“…Our results contrast with other culture-independent studies that showed a significant percentage of sequences remained unclassified [7,63]. The success of the current study may be related to the fact that most of the microbiota thriving in the phylloplane is readily cultivable [26,56], but also because the identification approach used relied on phylogenetic inference (by means of the OPU approach) [21] and not just on sequence identity clustering (classification by means of OTU clustering and blast matches of their representatives), as commonly used [7,17,26].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our results contrast with other culture-independent studies that showed a significant percentage of sequences remained unclassified [7,63]. The success of the current study may be related to the fact that most of the microbiota thriving in the phylloplane is readily cultivable [26,56], but also because the identification approach used relied on phylogenetic inference (by means of the OPU approach) [21] and not just on sequence identity clustering (classification by means of OTU clustering and blast matches of their representatives), as commonly used [7,17,26].…”
Section: Discussioncontrasting
confidence: 86%
“…In previous studies [21,65], OTUs were defined by clustering the units according to an identity threshold. Here, the OTUs based on MALDI-TOF/MS measures corresponded to each independent cluster formed by profile identity limits, which were dependent on each dataset.…”
Section: Otu and Opu Definitions In This Studymentioning
confidence: 99%
“…This study may be regarded as one with the largest set of identified cultures obtained from environmental samples. Although this culture set may seem small compared to the one of 284,899 clinical isolates [45], it is comparable to the 3626 isolates from bottled natural mineral water identified by random amplified polymorphic DNA (RAPD) fingerprinting and 16S rRNA gene analyses [16]. MALDI-TOF/MS profiling has been shown to be very advantageous for analyzing the microbial diversity of the cultured fraction of environmental samples [34].…”
Section: Discussionmentioning
confidence: 85%
“…Complete sequences were used to reconstruct de novo trees using the neighbor-joining algorithm, while the partial sequences were added into a pre-existing tree using the ARB-Parsimony tool, both implemented in the ARB software package. Sequences were grouped in operational phylogenetic units (OPUs) as an alternative to using strict cut-off values of identity thresholds in order to identify isolated clades derived from the phylogenetic tree topology that produce biologically meaningful units [16,29]. An OPU was considered as the smallest clade containing one or more amplified sequences affiliating together with reference sequences available in the public repositories.…”
Section: Tree Reconstructionsmentioning
confidence: 99%
“…Random amplified polymorphic DNA (RAPD) analysis was used as primary fingerprinting method to recognize genomic diversity among the isolates following procedures described before (França et al 2015). Representative strains of each unique RAPD profile were selected.…”
Section: Methodsmentioning
confidence: 99%